Systolic Blood Pressure Mediates Body Mass Index and Non-alcoholic Fatty Liver Disease: A Population-Based Study - Guan, Xue; Zhang, Qian; Xing, Jie; Chen, Shuohua; Wu, Shouling; Sun, Xiujing (Turkish Journal of Gastroenterology, 2021)
Background: Background/Aims: Non-alcoholic fatty liver disease (NAFLD) is one of the most common chronic liver diseases. Systolic blood pressure (SBP) and body mass index (BMI) are associated with NAFLD. We aimed to evaluate the mediating effect of SBP in the association between BMI and NAFLD. Methods: A total of 21 072 participants were enrolled. Multivariate logistic regression and linear regression models were used to describe the association between BMI, SBP, and NAFLD. The impact of SBP on the association between BMI and NAFLD was determined through mediation analysis. Results: BMI was positively associated with incident NAFLD overall (odds ratio (OR) = 1.171, 95% CI (1.153-1.189)) and in the female (OR = 1.189, 95% CI (1.157-1.222)) and male groups (OR = 1.162, 95% CI (1.141-1.184)) (P < .001). SBP also showed positive effects in the general, female, and male groups (P < .001). The effect of BMI on SBP also indicated similar positive results in the general (β = 0.913, 95% CI (0.799-1.026)), female (β = 0.956, 95% CI (0.760-1.151)), and male (β = 0.867, 95% CI (0.727-1.006)) groups (P < .001). Mediation analysis showed that SBP contributed to 14.23% of the relationship between BMI and NAFLD in the general group and 31.07 and 22.67% of the relationship in the female and male groups of individuals younger than 50 years old, respectively. The mediation effect appeared higher among females than among males, especially in participants younger than 50 years. Conclusion: SBP and BMI contribute to the development of NAFLD. SBP mediates a positive association between BMI and NAFLD among individuals younger than 50 years, especially among females.